Redesain SMP Muhammadiyah 13 Boyolali dengan Pendekatan Penghawaan dan Pencahayaan Alami - Yuliyanto, achmad, Wisnu Setiawan, ST., M.Arch.,Ph.D (2017)
Education in Boyolali is still said to be spreading. In the city of perhaps many of us have encountered schools stands, different from what we find in the village, just a simple building or may be said to be inadequate in supporting the education of students. The success of education programs in the learning process is influenced by several factors, namely students, curriculum, staff, infrastructure and facilities, addition to these factors environmental factors also influence the learning process. Building design concept that takes into account the natural environment by utilizing natural air and daylighting can make the classroom feel comfortable. With the redesign of Junior Hight School Muhammadiyah 13 are expected in the future can improve student achievement and creating high quality graduates as well as making the school is no less of a school located in the city center in terms of quality of teachers teaching, student support facilities, and building a safe and comfortable.